2002
DOI: 10.1007/s10096-002-0758-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Underlying Diseases and Prognosis Factors Associated with Pneumocystis carinii Pneumonia in Immunocompromised HIV-Negative Patients

Abstract: The aim of this retrospective study was to determine the underlying diseases associated with Pneumocystis carinii pneumonia (PCP) in immunocompromised HIV-negative patients and to identify prognosis factors in this population. One hundred three cases of PCP were diagnosed over a 5-year period. Diagnosis was established on the basis of clinical features and by detection of Pneumocystis carinii cysts in bronchoalveolar lavage fluid. Underlying diseases comprised hematologic malignancies (n=60; 58%), inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
30
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(35 citation statements)
references
References 52 publications
4
30
1
Order By: Relevance
“…Deaths were lowest for AIDS patients and highest for HSCT recipients, and rates in our study were consistent with earlier data ( 6 , 12 ). Microbial co-infection rates in our study were also in agreement with earlier data ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Deaths were lowest for AIDS patients and highest for HSCT recipients, and rates in our study were consistent with earlier data ( 6 , 12 ). Microbial co-infection rates in our study were also in agreement with earlier data ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Through multivariate analysis, we found that solid-organ transplantation was significantly associated with a better outcome. Previous reports have shown that mortality rates vary according to underlying disease or condition among non-HIV-infected patients with PCP (3)(4)(5). A Dutch group reported that the overall mortality rate was 35% among 78 HIV-negative patients, with the lowest rate (8%) among 13 kidney transplant recipients (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PCP has been reported with increasing frequency in non-HIV-infected patients, particularly in those with underlying immunosuppressive conditions such as hematologic malignancies, solid tumors, collagen vascular diseases, and solidorgan transplants and those receiving immunosuppressive therapies (2,3). Although clinical outcomes of PCP in HIV-infected patients have improved with the introduction of antiretroviral therapy, mortality rates among other immunocompromised patients with PCP who do not have HIV remain high at 30% to 60% (3)(4)(5). Identifying potential prognostic factors in non-HIV-infected patients with PCP could help clinicians make therapeutic decisions, such as choosing the appropriate site of care (intensive care unit versus general ward) or level of patient monitoring.…”
mentioning
confidence: 99%
“…The clin-ical presentation of PCP in HIV-negative patients is more severe than in HIV-positive patients, leading to estimated mortality rates of 40% and 15%, respectively (20)(21)(22). This is probably due to differences in the pathophysiology of the disease, and particularly in the host immune response.…”
mentioning
confidence: 98%